(untitled) (Eurasian Journal of Philology Science and Education, 2021)
Actually, American literature is formed in the first half of the XIX century. One of the poets who stood in at the origins of this literature was J. G. Whiter, who is better known for his abolitionist works. He deliberately limited the subject matter of the works, which made the verses simpler, both in form and in language, accessible to ordinary people. It was in this that the criticism of subsequent years saw the shortcomings of his works. His works remained a fact of literature of his time and are currently of interest only to researchers. USA literature originated in American romanticism. The origins of American poetry proper were many poets, each of whom contributed to the formation of a national identity of this literature. One of them was John Greenleaf Whittier, who before the Civil War deliberately subjugated his talent to abolitionism and went down in the history of American literature as an abolitionist poet. The object of the study is the work of the American poet of the 19th century, one of the instigators of American poetry itself and the prominent abolitionist poet John Greenleaf Whittier. The subject of research are poems and poems by J. G. Whittier. The purpose of the study is to determine the place of J. G. Whityere in American literature. The achievement of the indicated goal is due to the solution of the following tasks: to consider the poet’s creative path; to reveal the originality of the poetry of J. G. Whittier; determine its place in the history of American literature. The scientific novelty of the study is that the author is trying to reconsider the views established on the creative heritage of J. G. Whittier in modern American and partly in Russian literary criticism, which, recognizing his undeniable merits to American literature, consider him more as a fact of the history of literature.